Implementasi Key Performance Indicator pada Sistem Informasi Penilaian Kinerja Organisasi Himpunan Mahasiswa Jurusan Sistem Informas - Rahman Rahman; M. Fajratul Ikhsan (System Information and Computer Technology (SYNCTECH), 2024)
The evaluation of the Information Systems Department Student Association is a critical component in ensuring the organization’s success and long-term sustainability. However, the current assessment system relies heavily on subjective judgments and opinions, which may not accurately reflect the actual performance of the organization. Therefore, there is a need to implement a system that can objectively and accurately measure organizational performance over a defined period using the Key Performance Indicators (KPI) method. This approach should include clear success indicators, such as the execution of work programs within the specified timeframe, the achievement of the association’s vision and mission, and the level of member participation in each activity. The final outcome of this research is the development of a web-based Organizational Performance Assessment System that is both effective and accurate. The results of the system’s implementation demonstrate that the KPI method used in the Information System can support systematic performance evaluations and provide measurable, accountable insights into the achievement of organizational goals.mThe system utilizes five key performance indicators: the Scientific Division, the Communication and Information Division (Kominfo), the Regeneration Division, the Public Relations Division (PR), and the Secretarial and Logistics Division (Keslog). Each of these divisions plays a vital role in performance evaluation based on the KPI framework.